THE ORGANOLEPTIC AND MICROBIAL QUALITY OF SOME HERBAL MEDICINAL PRODUCTS MARKETED IN FREETOWN, SIERRA LEONE. - Kanu, Abdulai; Igbeneghu, Oluwatoyin; Orafidiya, Lara O (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
The WHO has advocated for the integration of herbal medicinal products into the primary health care system of developing countries. Safety, however, is a concern to the drug regulatory bodies. This study was carried out to determine the organoleptic properties and the microbial quality of herbal products available to consumers in the Freetown metropolis of Sierra Leone. Twenty herbal preparations purchased within the Freetown metropolis were assessed for taste, colour, odour, and pH. The microbial load and the presence of pathogens were determined. The residual antibacterial activity of two preparations that showed no microbial contamination was determined using the cup plate method. The ability of a combination of methyl- and propyl-parabens to prevent growth in some of the herbal products was studied. The study showed that 80% of the samples contained mean bacterial and fungal counts ranging from 1.47 x 108 to 9.375 x 108cfu/ml and 3.45x108 to 1.6x109cells/ml, respectively. The bacterial contaminants were predominantly Gram-positive organisms of the genera Bacillus and Staphylococcus. Escherichia coli, Salmonella spp. and Shigella spp. were among the isolated pathogens. The moulds, Aspergillus spp. and Trichoderma harzianum, and the yeasts, Candida albicans and Cryptococcus neoformans, were predominant fungal contaminants. The apparently non-contaminated herbal samples inhibited test organisms while the preservative system completely inhibited growth in the tested samples. The results suggest that many of the herbal medicinal preparations marketed in Freetown are likely to be contaminated with potentially pathogenic microorganisms. The quality of these herbal products may however be improved by the incorporation of appropriate preservatives.